1969
DOI: 10.1073/pnas.62.3.821
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation of Two Enzyme-Ribonucleic Acid Complexes Involved in the Synthesis of Foot-and-Mouth Disease Virus Ribonucleic Acid

Abstract: Abstract.-The foot-and-mouth disease virus-RNA polymerase complex was released from membrane particulates present in the cytoplasm of infected baby hamster kidney cells. The soluble polymerase complex was fractionated by zonal centrifugation in sucrose gradients. Two polymerase complexes (RNA and protein complex) active in the cell-free system were isolated and had S-rate ranges of 20-70S and 100-300S, respectively. The light polymerase complex contained 20S double-stranded RNA; and the heavy polymerase comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

1970
1970
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 13 publications
1
18
1
Order By: Relevance
“…Poliovirus RNA polymerase activity is easily measured in crude extracts (6, 7), but the lack of a suitable purification procedure has prevented the identification of the viral polypeptides necessary for the enzymatic activity. Previous attempts to purify the polymerase activity from picornavirus-infected cells have shown that the polymerase activity sediments as a membraneassociated complex of 60-250 S (8)(9)(10)(11)(12)(13)(14) and is associated with many viral polypeptides (15).…”
mentioning
confidence: 99%
“…Poliovirus RNA polymerase activity is easily measured in crude extracts (6, 7), but the lack of a suitable purification procedure has prevented the identification of the viral polypeptides necessary for the enzymatic activity. Previous attempts to purify the polymerase activity from picornavirus-infected cells have shown that the polymerase activity sediments as a membraneassociated complex of 60-250 S (8)(9)(10)(11)(12)(13)(14) and is associated with many viral polypeptides (15).…”
mentioning
confidence: 99%
“…FMDV, as member of the Picornaviridae , has a similar genome organization and is believed to follow a similar replication strategy to poliovirus [22]. In contrast to poliovirus, replication and translation of FMDV RNA occurs in the cytoplasm [23], and a replication complex of FMDV and its possible association with cellular membranes has not yet been described in detail. However, our research with a QD-sdAb probe demonstrates that mature FMD virions are located on one side of the cell nucleus as the time after inoculation increases.…”
Section: Discussionmentioning
confidence: 99%
“…Lodish and Zinder (1966) presented an evidence that two RNA polymerases participated in the synthesis of bacteriophage f2 RNA. Lately, Arlinghaus and Polatnick (1969) isolated two vRNA polymerase-RNA complexes from foot-and-mouth disease virus-infected cells.…”
Section: Discussionmentioning
confidence: 99%